Answer:
2
Step-by-step explanation:
Use rise over run (y2 - y1) / (x2 - x1)
Plug in the points:
(6 + 6) / (2 + 4)
12/6
= 2
So, the rate of change is 2
1. 2x+3=4x+2
⇒ 4x-2x=3-2
2x=1
x=1/2
There is one solution.
2. 18p-10p=5+6/2
8p=5+3
8p=8
p=8:8
p=1
3. 6a/3=2a
2a-a= -2 -3
a= - 5
4. 5+r-2=9,
5-2+r=9
3+r=9
r=9 - 3
r=6
5. -0,9 m= 9
m= - 10
6. -2 (x+1/4)=5-1=4
x+1/4= -2
x= -2 - 1/4
x= -8/4 - 1/4= - 9/4
7. 6f+4f= 6 + 12
10 f = 18
f=18/10=1,8
8. 7n - 3n= 16
4n=16
n=16:4
n=4
9. 1/3m-5/6m= - 15 - 3
2/6 m-5/6=-18
- 3/6m=-18 ⇒ 1/2m=18
m=2*18=36
11.4 should be the answer
if you mean tens then it is 10
we are given
point-A= -7
point-B=8
(a)
opposite of point-A is negative of point-A value
so,
opposite of point-A is -(-7)
opposite of point-A is 7
opposite of point-B is negative of point-B value
so,
opposite of point-B is -8
opposite of point-B is -8
(b)
we can see that
opposite of point-A is 7
opposite of point-B is -8
they are not equal
so, this argument is FALSE.......Answer